2018
DOI: 10.1126/sciadv.aar5471
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity reveals hidden resistance to extinction under climate change in the global hotspot of salamander diversity

Abstract: Integrating physiological and behavioral plasticity into climate change models markedly reduces predicted extinction risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 67 publications
4
108
0
Order By: Relevance
“…Yan et al () and Liang et al () uncovered seven divergent mitochondrial clades in A. davidianus . Besides, Riddell, Odom, Damm, and Sears () revealed that plasticity may contribute in buffering salamander species from climate change. Models not accounting for plasticity may overestimate a species' extinction risk.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al () and Liang et al () uncovered seven divergent mitochondrial clades in A. davidianus . Besides, Riddell, Odom, Damm, and Sears () revealed that plasticity may contribute in buffering salamander species from climate change. Models not accounting for plasticity may overestimate a species' extinction risk.…”
Section: Discussionmentioning
confidence: 99%
“…For one species (the Rough-skinned Newt, Taricha granulosa), individuals occupying a coastal stream on the Pacific Coast of North America varied in their physiological tolerance to elevated salinity, with individuals closer to the ocean exhibiting less of a response to salt stress than those found farther upstream(Hopkins et al, 2016). Physiological plasticity is a significant means by which species may persist across varying environmental conditions(Chevin & Hoffmann, 2017;Herrando-Pérez et al, 2018;Novarro et al, 2018).Ultimately, plasticity may buffer some species from extinction by promoting physiological, behavioral, and/or other adaptations that could minimize potentially lethal exposure to stressors such as salinity(Chown et al, 2010;Riddell, Odom, Damm, & Sears, 2018;Sergio, Blas, & Hiraldo, 2018;Urban, Richardson, & Freidenfelds, 2014).…”
mentioning
confidence: 99%
“…When environmental temperature changes, animals can respond by behaviourally thermoregulating (including migration, seeking shade or panting) (Walther et al 2002;Sunday et al 2010;Campbell et al 2018), they can adapt over many generations (Fields et al 1993;Hendry and Kinnison 1999;Kinnison and Hendry 2001;Parmesan and Yohe 2003;Root et al 2003;Charmantier et al 2004;Gienapp et al 2008), or they can acclimate, by shifting their thermal performance curves to better match environmental temperatures (Wilson and Franklin 2002;Riddell et al 2018;Rohr et al 2018). Thermal acclimation, a form of reversible plasticity, occurs when an organism shifts their underlying physiology in response to a change in environmental temperature to maintain physiological function (Wilson and Franklin 2002;Beaman et al 2016) (Fig 1.2).…”
Section: Thermal Acclimationmentioning
confidence: 99%
“…The ability B. cocosensis has to acclimate may buffer them from increased temperatures associated with climate change, and some studies suggest that plasticity is already protecting some species from climate warming (Rohr et al 2018;Riddell et al 2018). Extreme heat events, however, are predicted to result in local population extinctions , as rate of thermal change is likely to be faster than rates of physiological change/acclimation (Peck et al 2009).…”
Section: Maximum Ventilation Ratementioning
confidence: 99%
See 1 more Smart Citation